IMPACT OF RENEWABLE ENERGY CONSUMPTION, INDUSTRIALIZATION, AND TRADE OPENNESS ON CARBON EMISSIONS AMID URBANIZATION AND ECONOMIC GROWTH: A STUDY OF 9 ASEAN COUNTRIES - Ahmad Aqil Widyantoro; Eva Idvi Nugrahani; Zarel Saessatya; Indah Susilowati; Mentari Anggun Djatayu; Zulfikar Al-Hafidz; Saifan Nasri (RADJA PUBLIKA, 2025)
This study investigates the impact of renewable energy consumption, industrialization, urbanization, trade openness, and economic growth on carbon emissions in nine ASEAN countries namely Indonesia, Malaysia, the Philippines, Singapore, Thailand, Vietnam, Laos, Cambodia, and Brunei over the period 1994 to 2023. Using panel data regression methods with Fixed Effect Model (FEM) and Common Effect Model (CEM) based on Chow and Hausman tests, the results show that renewable energy consumption has a statistically significant negative effect on carbon emissions. In contrast, industrialization, trade openness, and economic growth exert positive influences. Urbanization presents varied effects depending on the country's development level and institutional quality. These findings provide empirical evidence supporting the role of renewable energy in emissions reduction, while also highlighting the environmental risks associated with rapid industrial and economic expansion in the absence of sustainable policies. Policymakers are advised to design integrated energy, industrial, and trade policies that align with regional low-carbon development goals and to strengthen cooperation under the ASEAN Plan of Action for Energy Cooperation (APAEC) framework. Keywords: Carbon emissions; Industrialization; Renewable energy; Trade Openness; Urbanization